Pengaruh Retur on Equity, Earning per Share, dan Nilai Tukar terhadap Return Saham Industri Pangan di BEI 2016-2019 - Gendro Wiyono; Vinsensius Uran; Alfiatul Maulida (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The purpose of this study was to analyze the effect of return on equity (ROE), earnings per share (EPS), and exchange rates on stock earnings. The population used in this study were producers in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) in the 2016-2019 period, namely 11 companies and 52 samples of financial statements determined using purposive sampling. Based on the results of the analysis in this study, it can be concluded that return on equity (ROE) and the exchange rate have a positive effect on stock returns. Meanwhile, Earning Per Share (EPS) has a negative effect on stock returns. Keywords: ROE, EPS, exchange rate, stock returns